Navigating Bureaucratic Complexity through Social Networks and Human Capital in Informal Governance - Nur, Zeynap (Bulletin of Science, Technology and Society, 2025)
This study investigates the interplay between social networks and human capital in facilitating informal governance mechanisms within public organizations. Through a comprehensive literature review, the research examines how informal structures complement formal bureaucratic processes, enabling individuals and organizations to navigate complex administrative environments. The analysis highlights the role of social networks in fostering collaboration, enhancing information flow, and promoting adaptability. Simultaneously, human capital—encompassing skills, knowledge, and experience—empowers individuals to leverage these networks effectively. The findings underscore the significance of integrating informal governance mechanisms into public administration practices to address multifaceted challenges and improve service delivery. By recognizing and harnessing the potential of social networks and human capital, policymakers and practitioners can enhance organizational performance and responsiveness. The study contributes to the discourse on governance by elucidating the value of informal structures in navigating bureaucratic complexity.